The burden of community-acquired pneumonia in the elderly: the Spanish EVAN-65 Study - Grive Montserrat; Maxenchs Monica; Arija Victoria; de Diego Cinta; Vila-Córcoles Angel; Ochoa-Gondar Olga; Martin Enrique; Pinyol Josep L (BMC, 2008)
Abstract Background Community-acquired pneumonia (CAP) is generally considered a major cause of morbidity and mortality in the elderly. However, population-based data are very limited and its overall burden is unclear. This study assessed incidence and mortality from CAP among Spanish community-dwelling elderly. Methods Prospective cohort study that included 11,240 individuals aged 65 years or older, who were followed from January 2002 until April 2005. Primary endpoints were all-cause CAP (hospitalised and outpatient) and 30-day mortality after the diagnosis. All cases were radiographically proved and validated by checking clinical records. Results Incidence rate of overall CAP was 14 cases per 1,000 person-year (95% confidence interval: 12.7 to 15.3). Incidence increased dramatically by age (9.9 in people 65-74 years vs 29.4 in people 85 years or older), and it was almost double in men than in women (19.3 vs 10.1). Hospitalisation rate was 75.1%, with a mean length-stay of 10.4 days. Overall 30-days case-fatality rate was 13% (15% in hospitalised and 2% in outpatient cases). Conclusion CAP remains as a major health problem in older adults. Incidence rates in this study are comparable with rates described in Northern Europe and America, but they largely doubled prior rates reported in other Southern European regions.